Preparation of rice straw-waste tire dust composite board - Muhammad Syafiq Azmi (Universiti Malaysia Perlis, 2009)
In this study agricultural lignocelluloses fiber (rice straw) and waste tire dust composite board were prepared using the method use in the wood-based panel industry. The manufacturing parameters were density (0.66g/cm3, 0.64 g/cm3, 0.60 g/cm3) and rice straw content(10/90, 20/80 and 30/70) weight of rice straw/waste tire dust of 10,20 and 30wt%. A commercial polyurethane adhesive for rubber was used as the composite binder. Water absorption and thickness swelling properties of the composite board were highest that wood-based panel board. The composite board prepared with rice straw and waste tire dust had a lower modulus of elasticity (MOE) value than wood-based particle board thus had better flexural properties than the wood particle board. Scanning electron microscopy (SEM) micrograph of the composite board showed all the tire dust powder are cured at the hot pressing temperature 150ºC and bind with the rice fiber. The rice straw-waste tire dust composite board can be used for specific purpose such as for producing flexural material.